Emotional prosody modulates attention in schizophrenia patients with hallucinations - Alba-Ferrara, Lucia; De Erausquin, Gabriel A.; Hirnstein, Marco; Weis, Susanne; Hausmann, Markus (Frontiers in Human Neuroscience, 2013)
Recent findings have demonstrated that emotional prosody (EP) attracts attention involuntarily (Grandjean et al., 2008). The automat shift of attention toward emotionally salient stimuli can be overcome by attentional control (Hahn et al., 2010). Attentional control is impaired in schizophrenia, especially in schizophrenic patients with hallucinations because the “voices” capture attention increasing the processing load and competing for top-down resources. The present study investigates how involuntary attention is driven by implicit EP in schizophrenia with auditory verbal hallucinations (AVH) and without (NAVH). Fifteen AVH patients, 12 NAVH patients and 16 healthy controls (HC) completed a dual-task dichotic listening paradigm, in which an emotional vocal outburst was paired with a neutral vocalization spoken in male and female voices. Participants were asked to report the speaker's gender while attending to either the left or right ear. NAVH patients and HC revealed shorter response times for stimuli presented to the attended left ear than the attended right ear. This laterality effect was not present in AVH patients. In addition, NAVH patients and HC showed faster responses when the EP stimulus was presented to the unattended ear, probably because of less interference between the attention-controlled gender voice identification task and involuntary EP processing. AVH patients did not benefit from presenting emotional stimuli to the unattended ear. The findings suggest that similar to HC, NAVH patients show a right hemispheric bias for EP processing. AVH patients seem to be less lateralized for EP and therefore might be more susceptible to interfering involuntary EP processing; regardless which ear/hemisphere receives the bottom up input.